After-discharges and seizures during pediatric extra-operative electrical cortical stimulation functional brain mapping: Incidence, thresholds, and determinants. Issue 10 (October 2017) - Aungaroon, Gewalin; Zea Vera, Alonso; Horn, Paul S.; Byars, Anna W.; Greiner, Hansel M.; Tenney, Jeffrey R.; Arthur, Todd M.; Crone, Nathan E.; Holland, Katherine D.; Mangano, Francesco T.; Arya, Ravindra
Highlights: Electrical cortical stimulation shows high incidence of after-discharges (77%) and seizures (35%) Current thresholds for after-discharges show a significant linear decreasing trend with age. After-discharges predict 3.5 times higher odds of having a seizure during cortical stimulation. Abstract: Objective: This study examined the incidence, thresholds, and determinants of electrical cortical stimulation (ECS)-induced after-discharges (ADs) and seizures. Methods: Electrocorticograph recordings were reviewed to determine incidence of ECS-induced ADs and seizures. Multivariable analyses for predictors of AD/seizure occurrence and their thresholds were performed. Results: In 122 patients, the incidence of ADs and seizures was 77% (94/122) and 35% (43/122) respectively. Males (odds ratio [OR] 2.92, 95% CI 1.21–7.38, p  = 0.02) and MRI-negative patients (OR 3.69, 95% CI 1.24–13.7, p  = 0.03) were found to have higher odds of ECS-induced ADs. A significant trend for decreasing AD thresholds with age was seen (regression co-efficient −0.151, 95% CI −0.267 to −0.035, p  = 0.011). ECS-induced seizures were more likely in patients with lateralized functional imaging (OR 6.62, 95% CI 1.36–55.56, p  = 0.036, for positron emission tomography) and presence of ADs (OR 3.50, 95% CI 1.12–13.36, p  = 0.043). Conclusions: ECS is associated with a high incidence of ADs and seizures. With age, current thresholds decrease and the probability for AD/seizure occurrence increases. Significance: ADs and seizures during ECS brain mapping are potentially hazardous and affect its functional validity. Thus, safer method(s) for brain mapping with improved neurophysiologic validity are desirable.